Dynamics of planar interface growth during directional solidification of alloys. (1st March 2015) - Fabietti, L.M.; Mazumder, P.; Trivedi, R.
Abstract : The dynamics of plane front growth during directional solidification is investigated in a well-characterized system of succinonitrile–acetone, and the results show significant deviations from the predictions of existing models. This discrepancy is shown to arise from the assumption of solidification from one end in the theories that ignore the presence of an initial solute boundary layer generally present in experiments. A numerical model that relaxes this assumption is presented that gives excellent agreement with the experimental results.